HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SERVIS BAWAH BOLA VOLI PADA SISWA PUTRA KELAS V SDN 003 PULAU PADANG KECAMATAN SINGINGI - WERSA’ADA '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is under service volleyball male students class V SDN 003 Pulau Padang District of Singingi not in good category either. This problem is suspected because of the muscle strength arm and shoulder possessed by the students. The purpose of this study was to prove the corealation muscle strength of arms and shoulders with the ability to under serve volleyball. The method used is the correlation method is a method used to determine the degree of correlation between the different variables. The population in this study were male students class V SDN 003 Pulau Padang Singingi District, which amounted to 14 people. The sample selection using total sampling technique thus the sample in this study were 14 male students. Analysis of data using correlation and regression analysis. Before testing the hypothesis to test hypotheses and analysis requirements for linearity test regression line by F test using a significance level of 5%. Obtained Fhitung = 5.41> F table = 4.60, and the regression equation is Y = 8:21 + 0.92X. Furthermore, to test the truth of the correlation between variables X and Y then tested the significance of using the formula t test of significance. From the calculation results are known t = 2.32, while table = 1.782. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is